Aging-related impairment of neurogenic chloride secretion in human colon mucosa - Ruiyun Wang; Jing He; Pengcheng Yang; Tao Bai; Jun Song; Xiaohua Hou; Lei Zhang (Frontiers in Physiology)
Backgroundlderly individuals are more susceptible to chronic constipation, which may be linked to imbalanced mucosa secretion and absorption. Our research aims to explore the age-related alterations in epithelial chloride secretion within the human colon.MethodsColonic mucosal tissues were obtained from 9 young patients (aged 28–35 years), 10 middle-aged patients (aged 48–56 years), 10 elderly patients without constipation (aged 66–75 years), and 12 elderly patients with constipation (aged 65–78 years) who underwent surgery for colonic carcinoma. The epithelial chloride (Cl−) secretion was assessed using the short-circuit current (Isc) method. Comparative analysis was conducted on Cl− secretion induced by spontaneous activity, bethanechol, forskolin, veratridine, and electrical field stimulation (EFS) in the four groups. Additionally, investigations were carried out on changes in cholinergic and VIPergic Cl− secretion.ResultsThe spontaneous Cl− secretion was not affected by aging. The increase in Isc induced by bethanechol and forskolin remained unaltered in aged colon. However, the veratridine-induced neurogenic Isc increment were significantly reduced with aging and constipation. The EFS-evoked Isc rising, which typically exhibiting a biphasic pattern, was inhibited by aging in a frequency-dependent manner. Administration of scopolamine and VIP6-28 to block cholinergic and vasoactive intestinal peptide (VIP) receptors led to smaller increases in the first and second phases of the EFS-evoked response in aged colons compared to young colons.ConclusionSignificant impairments in neurogenic Cl− secretion occur in the aged colon, correlating with the degeneration of cholinergic and VIPergic nerves in the mucosa. This study could enhance our understanding of the pathophysiology of elderly constipation.